Detrimental interactions of neonicotinoid pesticide exposure and bumblebee immunity. Issue 5 (1st August 2017) - Czerwinski, Mitchell Andrew; Sadd, Ben Michael
GRAPHICAL ABSTRACT: Field realistic doses of a neonic pesticide compromise bumblebee constitutive and induced humoral immunity, and reduce immune‐challenged bee survival. Pesticide–immune interactions may enhance negative outcomes of pesticide–pathogen coexposure. Abstract: Pesticides are well known to have a number of ecological effects. However, it is only now becoming understood that sublethal exposures may have effects on nontarget insects of conservation concern through interactions with immunity, thus increasing detrimental impacts in the presence of pathogens. Pesticides and pathogens are suggested to have played a role in recent declines of several wild bee pollinators. Compromised immunity from exposure to widely used neonicotinoids has been demonstrated in honeybees, but further research on interactions between neonicotinoids and immunity in other important bees is lacking. In this study, adult workers of the bumblebee Bombus impatiens received 6‐day pulses of either low (0.7 ppb) or high (7 ppb) field realistic doses of the neonicotinoid imidacloprid prior to assaying immunity and survival following a nonpathogenic immune challenge. High‐dose imidacloprid exposure reduces constitutive levels of phenoloxidase, an enzyme involved in melanization. Hemolymph antimicrobial activity initially increases in all groups following an immune challenge, but while heightened activity is maintained in unexposed and low imidacloprid dose groups, it is not maintained in the high exposure dose bees, even though exposure had ceased 6 days prior. Additionally, imidacloprid exposure followed by an immune challenge significantly decreased survival probability relative to control bees and those only immune challenged or imidacloprid exposed. A temporal lag for immune modulation and combinatorial effects on survival suggest that resource‐based trade‐offs may, in part, contribute to the detrimental interactions. These interactions could have health consequences for pollinators facing multiple stresses of sublethal neonicotinoid exposure and pathogens.